The Influence Of Good Corporate Governance On Financial Performance in Sharia Banking 2019-2023 - Sellina, Sesri; Zed, Etty Zuliawati; Kartini, Tri Mulyani (Review: Journal of Multidisciplinary in Social Sciences, 2025)
This research aims to examine and analyze the influence of independent commissioners, audit committees, and the Sharia Supervisory Board (DPS) on financial performance. The population in this study is Islamic banking registered with the OJK from 2019-2023. In this study, the sample obtained consisted of 13 Islamic banks, selected using the purposive sampling method. This research uses secondary data obtained through literature review and documentation. The analysis method used in this research is the Econometric Views 12 (EViews12) software. The research results show that the audit committee and the Sharia Supervisory Board (DPS) have an impact on financial performance, but independent commissioners do not have an impact on financial performance.